The Difference of Serum Vitamin E Levels between Adolescent Patients with and without Acne Vulgaris - Wahyunita Desi Ratnaningtyas; Sawitri Sawitri; Dwi Murtiastutik; Afif Nurul Hidayati (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Acne vulgaris (AV) is a chronic inflammatory disease of the pilosebaceous unit, particularly among adolescents. The pathogenesis of AV is multifactorial, developing research studies the role of free radicals and antioxidants imbalance that cause oxidative stress in AV. The main antioxidant found in the skin is vitamin E, which functions as a protector against lipid peroxide. Purpose: To compare serum vitamin E levels in adolescents with AV and healthy adolescents without AV (controls). Methods: This is a cross-sectional observational analytic study that involved 17 adolescents with AV and 17 controls in Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Academic Hospital Surabaya. The subjects have met the inclusion and exclusion criterias. Result: The mean of vitamin E level in adolescent patients with AV was 7.8 ± 1.07 mg/mL and 10 ± 1.06 mg/mL in controls with the p-value in this study was p = 0.0001. Conclusion: It was found that serum vitamin E levels in adolescent AV patients were significantly lower than the controls. Further research is required to find out more about the role of antioxidants in the pathogenesis of AV.